(untitled) (Cadernos ESP, 2021)
The objective of the study is to report the experience of using agile methodology not following the flow of services for ELMO training. Project management following agile hybrid methodology, SCRUM wrapping model and Kanban fermentation. Data include continuous monitoring of metrics recorded in tables, tables and graphs, for the period from January to July 2021. 1443 health professionals were trained. It registered a total of 79 activities, with 5% (n = 4) in "delay", 8.9% (n = 7) in "refining", 5% (n = 4) not "in progress", 25, 31 % (n = 20) “in progress” and 55.7% (n = 44) “completed”. Overall income was calculated at 0.45 activities / day. The use of simplified methodologies in public organizations promotes the optimization of teamwork and management of activities. Improved Technological Innovation follows information and the interlocution between demands, tracing satisfactory results, within the limitations of the current public service.